A Low Complexity Joint Iterative Multi-User Detection Decoding Receiver Based on Verified Message - Miao, Jiansong; Hu, Xuejia; Li, Weijie; Li, Hairui (2020 IEEE/CIC International Conference on Communications in China (ICCC), 2020)
The sparse code multiple access technology and polar code technology can meet the functional requirements of the three major scenarios of 5G. A SCMA system receiver can combine a multi-user detector with a polar code decoder, but it requires high computational complexity to obtain the ideal bit error rate (BER) performance. This paper proposes a joint iterative detection and decoding receiver (VJDD) scheme for transmitting verified messages based on a serial structure. This solution improves the iterative convergence speed of the receiver by transmitting verified messages to each node in the factor graph in time. Simulation results show that the VJDD scheme can reduce the computational complexity of the receiver on the premise of ensuring the performance of the receiver.